Prevention of the Spread of the COVID-19 Virus with an Online to Offline Shopping System with an Independent Self-Service Concept using a Miniature Solar-Powered Mobile Market - Anantha Zakharia; Irvan Hermala; Putie Maharani (PT FORMOSA CENDEKIA GLOBAL, 2023)
The participation of universities is highly expected in assisting economic recovery, so that economic turnover activities can continue without increasing the number of Covid-19 sufferers. In this case, universities provide solutions in the field of renewable energy as a source of electricity to support the efficiency of the prototypes produced. This activity was carried out by students and lecturers as a form of community service. Where the concept offered is online to offline to maintain shopping loyalty. Consumers can make transactions by selecting product quality, tasting the product, and tasting the product first and they do it in front of their house in the form of a solar-powered mobile market. The method used in the data collection process: the Preparation Stage, the Group Discussion Stage, the Capacity Building Implementation Stage: the Research Stage, the Data Analysis Stage. The conclusion from this study is that the community is enthusiastic, especially those living in housing because of the online to offline system (online ordering system, goods come offline, consumers can choose). For vehicles, it can save fuel because it uses a solar power engine.